Risk Minimization Measures for Blood Screening HIV-1 Nucleic Acid Amplification Technique Assays in Germany - Chudy, Michael (S. Karger Verlag für Medizin und Naturwissenschaften GmbH, 2014)
BACKGROUND: Several publications describe HIV-1 RNA false-negative results or viral load underquantitation associated with Communauté Européenne(CE)-marked qualitative or quantitative nucleic acid amplification technique (NAT) assays. 6 cases occurred during blood screening in Germany, with 2 of them causing HIV-1 transmissions to recipients of blood components. The implicated NAT assays were mono-target assays amplifying in different viral genome regions (gag or long terminal repeat). METHODS: Specimens characterized by HIV-1 NAT underquantitation or false-negative NAT results were comparatively investigated in CE-marked HIV-1 NAT systems of different design to identify potential reasons. The target regions of the viral nucleic acids were sequenced and these sequences compared to primers and probes of the assays. Potential risk minimization measures were considered for quantitative and blood-screening HIV-1 NAT systems. RESULTS: Nucleotide sequencing of the viral target region in cases of HIV-1 RNA underquantitation or false-negative test results revealed new HIV-1 variants that were mismatched with primers and probes used in some mono-target assays. So far, dualtarget NAT assays have not been associated with mismatch-based false-negative test results. From 2015, the Paul Ehrlich Institute will request HIV-1 NAT assays of dual-target design or an analogous solution for further reducing the risk in blood screening. CONCLUSION: HIV differs from other blood-borne viruses with regard to its fast evolution of new viral variants. The evolution of new sequences is hardly predictable; therefore, NAT assays with only 1 target region appear to be more vulnerable to sequence variations than dual-target assays. The associated risk may be higher for HIV-1 NAT assays used for blood screening compared to quantitative assays used for monitoring HIV-1-infected patients. In HIV-1 screening NAT assays of dual-target design may adequately address the risk imposed by new HIV-1 variants.